Nursing Practice Environment and Its Relation to Missed Nursing Care : A Scoping Review - Rahmah A Aloufi*, Maram A Banakhar, Duaa A Hafez (Innovative Journal of Medical and Health Sciences, 2020)
Objective: To examine the association between the practice environment of nursing and the missed care of nursing in a systematic way in the related literature. Methodology: An extensive search was conducted in CINAHL, ProQuest, ERIC, MEDLINE, Web of Science, PubMed, and Science Direct databases. the included studies were published during time period of 2015-2020 with full text. Results: A total of 110 studies were screened, out of which 19 studies were identified to be eligible as per fulfillment of inclusion/exclusion criteria. Degraded quality of nursing, inpatient complications, and mishaps, as well as negative patient outcomes, is examined as examples for results of missed nursing care. The nurses missed the process and task of providing important patient care because of the increased workload, less communication and poor working environment. Inadequate resources and staffing were the major factors that were linked with the events of missed nursing care. Conclusion: It is concluded that reducing and modifying the examined factors, such as poor working environment, inadequate staffing, less resources, poor communication among nurses or patients etc. may decrease the missed nursing care practice. In addition, the missed nursing can also be managed through the practical implementation of motivating positive work environment and safety culture of patients. These improvements and practical implementation will help to provide quality patient care and decrease the missed nursing care. Keywords: Practice environment, missed nursing care, Teamwork, communication, workload, resources.